Emissions of Parent, Nitro, and Oxygenated Polycyclic Aromatic Hydrocarbons from Residential Wood Combustion in Rural China - SHEN, Guofeng (2012)
Residential wood combustion is one of the important sources of air pollution in developing countries. Among the pollutants emitted, parent polycyclic aromatic hydrocarbons (pPAHs) and their derivatives, including nitrated and oxygenated PAHs (nPAHs and oPAHs), are of concern because of their mutagenic and carcinogenic effects. In order to evaluate their impacts on regional air quality and human health, emission inventories, based on realistic emission factors (EFs), are needed. In this study, the EFs of 28 pPAHs (EF(PAH28)), 9 nPAHs (EF(PAHn9)) and 4 oPAHs (EF(PAHo4)) were measured for residential combustion of 27 wood fuels in rural China. The measured EF(PAH28), EF(PAHn9), and EF(PAHo4) for brushwood were 86.7±67.6, 3.22±1.95×10(−2), and 5.56±4.32 mg/kg, which were significantly higher than 12.7±7.0, 8.27±5.51×10(−3), and 1.19±1.87 mg/kg for fuel wood combustion (p < 0.05). Sixteen U.S. EPA priority pPAHs contributed approximately 95% of the total of the 28 pPAHs measured. EFs of pPAHs, nPAHs, and oPAHs were positively correlated with one another. Measured EFs varied obviously depending on fuel properties and combustion conditions. The EFs of pPAHs, nPAHs, and oPAHs were significantly correlated with modified combustion efficiency and fuel moisture. Nitro-naphthalene and 9-fluorenone were the most abundant nPAHs and oPAHs identified. Both nPAHs and oPAHs showed relatively high tendencies to be present in the particulate phase than pPAHs due to their lower vapor pressures. The gas-particle partitioning of freshly emitted pPAHs, nPAHs and oPAHs was primarily controlled by organic carbon absorption.